Treatment of recurrent hiatal hernia, complicated by pleural empyema, mediastinitis and sepsis - M. A. Protchenkov; А. V. Reshetov; A. V. Litvinov; Y. F. Ukhimik; D. I. Vasilevskii; S. Yu. Dvoreckiy; A. L. Akopov (Вестник хирургии имени И.И. Грекова)
An observation of a rare complication of a hiatal hernia is presented – migration of the stomach with an antireflux cuff into the mediastinum with the development of acute gastric dilation, necrosis of the gastric wall in a 51-year-old woman. The effectiveness of stage-by-stage treatment of severe intrapleural complications of recurrent hiatal hernia accompanied by sepsis and multiple organ failure is shown.